LITERATURE REVIEW : PERBANDINGAN EFEKTIVITAS EKSTRAK PEPAYA (Carica papaya L.) SEBAGAI LARVASIDA ALAMI TERHADAP LARVA Aedes aegypti INSTAR III DAN IV - Gabriella Charles Singam; Arif Rahman Jabal; Indria Augustina (Fakultas Kedokteran, Universitas Palangka Raya, 2022)
Based on the types, DENV 2 and DENV 3 are the types of dengue found in Indonesia, but the dominant one is DENV 3 because this type of virus causes severe cases of dengue. The papaya plant is a highly potent plant of natural larvicide. The literature review to compare the effectiveness of the papaya (Carica papaya L.) of each concentration, LC50 and LC90 againts the death toll of Aedes aegypti mosquito larvae. The study uses a Systematic Literature Review, the sourse of the data used in this study is secondary data obtained from experimental research journals and retrieved from websites Google Scholar. The journal received was 10 national journals and 5 international journals. Ten journals using papaya leaf ethanol extract, 1 journal using papaya leaf filtrate, 1 journal papaya leaf juice, 1 journal papaya sead ethanol extract, 1 journal papaya sead and leaf ethanol extract, as well as ethanol extract of seed, leaf, bark, and papaya root 1 journal. Researchers on average use more papaya leaf compared to other parts of the papaya plant and each method of precessing and concentration is different for each journal. There are 14 journals that say that the higher the concentration is used, the more the larvae are Ae. aegypti was killed, where as 1 journal says that the lower the concentration, the more toxic the larvae will get Ae. aegypti.